1982
DOI: 10.1002/qua.560220219
|View full text |Cite
|
Sign up to set email alerts
|

Omission in a comparative study of the structure and properties of ClF2 and Cl3 radicals by CNDO/2 and INDO methods

Abstract: In a very recent note published in this Journal [I], De and Sannigrahi have performed CNDO/2 and INDO calculations on the ClFz and c 1 3 radicals in order to see whether predictions from such calculations tally with ab initio [2] and experimental findings [3,4]. Furthermore, the authors stated that "the proposed study would also throw some light on the relative performance of the CND0/2 and I N D O methods in the calculation of ground state properties of triatomic interhalogen, in general" [I]. We deem it appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio 15,[24][25][26] and semiempirical methods. 9,[27][28][29][30][31][32] Recently, additional interest in the trihalogens has been generated by novel time-resolved studies of the Br + I 2 reaction. 1,[33][34][35][36] From the results on this system, it appears that trihalogens, accessed through photodissociation of HX-YZ complexes, may be especially suitable for real-time studies of reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation